Conducting Interviews for News Stories - Ricky Telg; Lisa Lundy (EDIS, 2021)
This publication on interviews for news stories is the fifth of a five-part series on news media writing. This series also covers an introduction to news media writing, news writing for print, grammar and punctuation, and news writing for television and radio. Minor revision by Ricky Telg and Lisa Lundy and published by the UF/IFAS Department of Agricultural Education and Communication. 3pp.